Patient blood management in oncology in the Russian Federation: resolution to improve oncology care. - A. Hofmann (IP Habib O.N., 2020)
The huge global burden of oncological diseases is growing and measures to counter this complex challenge are high on national health agendas. The Russian National Long-Term Oncology Strategy 2030 defines priorities, goals and directions in the fight against cancer. Italso contains action plans for more effective prevention, earlier and more specific diagnosis and more effective treatment options. Against this backdrop, experts now suggest to complement standard oncology treatment strategies by adding Patient Blood Management (PBM). For many clinical disciplines where a low blood count and considerable blood loss are commonly encountered, this bundle of care is the new standard. Based on clinical and scientific evidence, it aims to optimise medical and surgical patient outcomes by clinically managing and preserving a patients blood. The principles of this comprehensive concept can and must be transferred to oncology, thus offering value in improving cancer care and the efficacy of medical institutions. Accumulating evidence demonstrates that anaemia and iron deficiency, but also thrombocytopenia, blood loss and coagulopathy are independent risk factors for adverse patient outcomes including morbidity, mortality, reduced quality of life and prolonged average length of hospital stay in both surgical and medical patients. For the timely and effective detection and correction of these risk factors, an international network of multi-disciplinary clinicians and researchers has developed PBM. The rapidly growing body of evidence for PBM not only shows improved patient outcomes, but also reduced resource utilisation including the use of allogeneic blood components. The reduction of allogeneic blood transfusion further improves patient safety and outcomes, since transfusion is another independent risk factor for adverse outcomes. Supported by WHO endorsements and following the recommendations of an increasing number of state or national health authorities, PBM is about to become a new standard of care. However, even though the aforementioned risk factors are highly prevalent in oncology settings due to chemo-/radiotherapy and the pathology of the disease, the integration of PBM in standard oncology treatment pathways is lagging behind. Thus, and in support of the Russian National Long-Term Oncology Strategy 2030 to improve quality of oncological care, with the support of the National Association of Specialists in PBM (NASPBM), the PBM Oncology Working Group of the Russian Federation was created, consisting of national and international experts in oncology and PBM. On July 9, 2020, the Working Group met to discuss the rationale for PBM in oncology and to assess the need to implement PBM in Russian oncology care. As a result, the Group recommended to include PBM as an integral part of standard oncology treatment pathways, delineated the action required from facilitating stakeholders in the Russian Federation, determined a roadmap for implementation and developed a national resolution as a call to action on the matter. Presented herein, this resolution acknowledges the global and local impetus to reduce cancer mortality, and the rationale for PBM interventions to improve patient outcomes and alleviate the social and economic burden of cancer on the healthcare system.